Virtual Reality Animal Rescue World: Pediatric virtual reality analgesia during just noticeable pressure pain in children aged 2–10 years old (crossover design) - Alrimy, Taima; Alhalabi, Wadee; Malibari, Areej A.; Alzahrani, Fatma Salih; Alrajhi, Sharifah; Alhalabi, Mohammed; Hoffman, Hunter G. (Frontiers in Psychology, 2022)
Background and Aims. Excessive pain during medical procedures is a worldwide medical problem. Most scald burns occur in children under 6, who are often undermedicated. Adjunctive Virtual Reality (VR) distraction has been shown to reduce pain in children aged 6-17 , but little is known about VR analgesia in young children. This study tests whether desktop VR (Animal Rescue) can reduce the just noticeable pressure pain of children aged 2-10. Methods. A within-subject repeated measures design was used. With treatment order randomized, each healthy volunteer pediatric participant underwent 3 separate brief cutaneous pressure stimuli under 3 conditions: 1) no distraction, 2). a verbal color naming task (no VR), and 3) a large TV-based desktop VR distraction. A hand-held Wagner pressure pain stimulation device was used to generate just noticeable pain sensations. Participants indicated when a steadily increasing nonpainful pressure stimulus first turned into a painful pressure sensation (just noticeable pain). Results. A total of 40 healthy children participated (43% aged 2-5 years; and 57% aged 6-10 years). Compared to the no distraction condition, the 40 children showed significant VR analgesia (i.e., a significant reduction in pain sensitivity during the VR Animal Rescue condition), t(39) = 9.83, p < .001, SD = 6.24. VR was also significantly more effective at reducing pain sensitivity vs. an auditory color naming task, t(39) = 5.42, p < .001, SD = 5.94. The subset of children aged 2-5 showed significant reductions in pain during VR. Children under 6 showed greater sensitivity to pain during no distraction than children aged 6-10. Conclusions. During no distraction, children under six years old were significantly more sensitive to pain than children aged 6-10. VR significantly reduced the “just noticeable” pressure pain sensitivity of children in both age groups.